In Utero Eye Development Documented by Fetal MR Imaging - Paquette, L.B.; Jackson, H.A.; Tavaré, C.J.; Miller, D.A.; Panigrahy, A. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: To date, very limited attention has been given to ocular abnormalities or growth parameters detected by fetal MR imaging. Our objective was to retrospectively determine the relationship between different parameters of eye development and estimated gestational age in the human fetus by use of fetal MR imaging. MATERIALS AND METHODS: A retrospective study was performed to measure the transverse diameter, interocular distance, and lens diameter of the globes of 127 fetuses who had a morphologically normal central nervous system. Multiple single-shot T2 fast spin-echo images were obtained with a 1.5T magnet by use of contiguous 3-mm intervals in at least 2 orthogonal planes. Loess curves were fitted to explore the relationship between gestational age and each of the 3 measurements of interest. Different models were compared statistically to determine the model of best fit. RESULTS: For each variable of interest, the “best” model of eye growth was a quadratic function. Specifically, lens growth seems to plateau after 36 weeks of gestation, interocular distance plateaus after 36 weeks of gestation, and globe growth plateaus after 42 weeks of gestation. CONCLUSIONS: The lens, orbit, and interocular distance growth of the fetus can be demonstrated on fetal MR imaging. All 3 measurements suggest a quadratic model of growth, which indicates slowing of growth toward the end of gestation.